Advanced Emissivity Tuning Via Femtosecond Laser Surface Engineering - Kamali Khanghah, Zahra; Butler, Andrew; Reicks, Andrew; Parmar, Juveriya; Schubert, Eva; Zuhlke, Craig; Schubert, Mathias ; 0000-0001-6238-663X; Kilic, Ufuk; Ghashami, Mohammad (Advanced Optical Materials, 2025)
Tuning the spectral and directional characteristics of thermal emission is critical for advancing technologies such as thermophotovoltaics (TPVs), passive thermal radiative cooling (PTRC), and solar thermophotovoltaics (STPVs), yet scalable fabrication methods remain limited. Here, femtosecond laser surface processing (FLSP), a top-down ablation and re-solidification approach is employed, to create mound-shaped surface microstructures on titanium (Ti) surfaces. By varying laser fluence and pulse count, spectrally selective and omnidirectional high emissivity (⩾0.9) in the mid-infrared range (7.5–14 µm) is achieved, which increases with structure height. To understand the underlying physics, finite element modeling (FEM) is conducted, guided by structural and optical parameters extracted using Mueller matrix spectroscopic ellipsometry and modeled via the anisotropic Bruggeman effective medium approximation. Simulations reveal that height, base length, periodicity, and oxide shell contribute to the emergence of plasmonic and interband resonance modes spanning the UV to mid-IR range. Comprehensive material characterizations, including SEM, FIB-EDS, and XPS, confirm the formation of a conformal Ti–TiOx core-shell interface, which activates mid-IR resonance modes in agreement with FEM predictions. The proposed Ti-based metamaterial platform provides a scalable strategy for engineering thermal emission in next-generation energy systems.
Keywords: femtosecond laser surface processing; spectral and directional emissivity; spectroscopic ellipsometry; titanium metamaterials